ANALISIS PENGARUH STRUKTUR KEPEMILIKAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP KETERLAMBATAN AUDIT - Sebriwahyuni, Raja Andiani; Kurniawan, Bagas (Faculty of Economics, Universitas Internasional Batam, 2020)
This main focus of this study is to analysis the effect of the company ownership and company growth on audit report lag. The target sample of this study consists of companies listed in Indonesian Stock Exchange (IDX) during 2014-2018. This study using purposive sampling method to collected data. There are 428 companies that required and proceed with panel regression to analyze the effect of independent variable on dependen variable. The result however show that only foreign ownership has significant impact on audit report lag, but managerial ownership, institutional ownership, company growth, and ownership concentration has insignificant impact on audir report lag.